Dampak Peringkat Pegawai Pada Hubungan Antara Sikap, Motivasi, dan Kinerja Pada Pemerintah Kota : (Studi Kasus Pada Pemerintah Kota Bandung) - Syahri Ramadani; Syaiful Rahman Soenaria (Universitas 45 Surabaya, 2024)
This study explores the impact of employee ranking on the correlation between attitudes, motivation, and performance in the Bandung City Government using a quantitative approach through a single case study. From 106 respondents surveyed through a questionnaire, the results show that employee ranking does not affect the relationship between attitudes, motivation, and performance. Factors such as work ethic, supervisor support, compensation satisfaction, and participation in setting performance standards play a more significant role in motivating employees. Feedback and involvement in setting performance standards are also more motivating than ranking. Fair compensation and transparency of information are crucial in enhancing motivation and performance. The study's limitations include a limited number of respondents and difficulty reaching respondents with high employment status. Future research is recommended to increase the number of respondents, develop hypotheses suited to the study environment, and use other moderating variables. Management needs to provide opportunities for skill enhancement and conduct regular evaluations of the ranking system to create a productive work environment.